What Lies Beneath? A Time‐varying FAVAR Model for the UK Transmission Mechanism. (May 2014) - Ellis, Colin; Mumtaz, Haroon; Zabczyk, Pawel
<x xml:space="preserve">Abstract</x> We use a time‐varying factor‐augmented VAR to investigate changes in the transmission mechanism of economic shocks in the UK. Our estimates demonstrate the importance of time variation and suggest that monetary policy shocks had a bigger impact on inflation, equity prices and the exchange rate during the inflation targeting period. Changes in the transmission of policy shocks to bond yields point to more efficient management of long‐run inflation expectations. Finally, we investigate responses of disaggregated prices, with the median becoming more negative and cross‐sectional patterns consistent with a decrease in the role of cost channels.